Women Intellectuals in Post-68 France : Petitions and Polemics - Long, Imogen; SpringerLink (Online service). (London : Palgrave Macmillan UK, 2013)
Accounts of public intellectuals in France and French feminism have focused on a specific set of women thinkers overlooking some major women intellectuals. This book aims redresses this balance by studying these forgotten intellectuals creating a cultural and theoretical re-evaluation of the gendered phenomenon of the public intellectual in France.
Keywords: Science; Science, general